Diagnosis and treatment of osteoporosis following hip fracture in Chiang Mai University Hospital. - Rojanasthien S. (2014)
BACKGROUND: Osteoporosis is defined as a skeletal disorder characterized by compromised bone strength predisposing a person to an increased risk of fracture. Hip fracture is the common and serious consequence of osteoporosis. To improve bone quality and prevent new fracture, osteoporosis should be treated while the patient was admitted with hip fracture problem. Several medications have been proven to be effective. Objectives of the present study were to determine the adequacy of diagnosis and treatment of osteoporosis in hip fracture patients. MATERIAL AND METHOD: A retrospective study of all low energy trauma hip fracture patients, between 1998 and 2003 at the age of 50 years old or more. The National Osteoporosis Foundation guideline was used to identify adequacy of diagnosis and treatment of osteoporosis in this group of patients. Age, sex, admitted diagnosis, mechanism of injury, admission medication, treatment procedures, discharge medication, BMD investigation were analysed. RESULTS: The percentage of calcium supplementation for the discharged patients in 1998 to 2003 was 0%, 10.5%, 33.3%, 32.7%, 39.3% and 43.0% respectively. The percentage of combination of calcium and vitamin D supplementation for the discharged patients was 0%, 8.8%, 21.1%, 12.7%, 24.6% and 37.5% respectively. Bisphosphonate was ordered in 9 and calcitonin in 20 patients. 7% of patients were diagnosied as osteoporosis. The quantity of osteoporosis was confirmed by DXA measurement in only one patient. CONCLUSIONS: In the past 6 years, most of the hip fracture patients were underdiagnosed and undertreated for osteoporosis. There was also a good trend for better treatment.